2003
DOI: 10.1038/nm935
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of renal cystic disease development and progression by a vasopressin V2 receptor antagonist

Abstract: The polycystic kidney diseases (PKDs) are a group of genetic disorders causing significant renal failure and death in children and adults. There are no effective treatments. Two childhood forms, autosomal recessive PKD (ARPKD) and nephronophthisis (NPH), are characterized by collecting-duct cysts. We used animal models orthologous to the human disorders to test whether a vasopressin V2 receptor (VPV2R) antagonist, OPC31260, would be effective against early or established disease. Adenosine-3',5'-cyclic monopho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
462
0
13

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 610 publications
(494 citation statements)
references
References 24 publications
19
462
0
13
Order By: Relevance
“…Recent findings support the utility of vasopressin agonists in patients with vasodilator shock (19) and the potential use of V2 antagonists in various diseases involving altered fluid retention, such as congestive heart failure, cirrhosis, nephrotic syndrome, and syndrome of inappropriate antidiuretic hormone secretion (58). Moreover, the V2-receptor antagonist OPC31260 has been suggested to slow progression polycystic kidney disease in mouse models, suggesting clinical trials of V2-receptor antagonist in PKD (24). By defining the sites of V1a-and V2-receptor expression in mouse and human kidney, the present studies should further inform results obtained using these pharmaceuticals in mouse and human.…”
Section: Discussionmentioning
confidence: 86%
“…Recent findings support the utility of vasopressin agonists in patients with vasodilator shock (19) and the potential use of V2 antagonists in various diseases involving altered fluid retention, such as congestive heart failure, cirrhosis, nephrotic syndrome, and syndrome of inappropriate antidiuretic hormone secretion (58). Moreover, the V2-receptor antagonist OPC31260 has been suggested to slow progression polycystic kidney disease in mouse models, suggesting clinical trials of V2-receptor antagonist in PKD (24). By defining the sites of V1a-and V2-receptor expression in mouse and human kidney, the present studies should further inform results obtained using these pharmaceuticals in mouse and human.…”
Section: Discussionmentioning
confidence: 86%
“…However, if we assume that the primary defect in type 2 ADPKD is PKD2-mediated Ca 2+ influx (and not Na + or K + which also pass through PKD2), it is possible that a connection between a Ca 2+ channel and cAMP can be made. It has been reported that cystic cells have abnormally high levels of cAMP [79][80][81][82] and the administration of a vasopressin V2 receptor antagonist, which reduced cAMP, suppressed the cystic phenotype in PKD2 knock out mice [83] and other animal models [84,85]. It is also known that store-operated Ca 2+ channels are directly coupled to specific isoforms of adenylyl cyclases [86][87][88].…”
Section: Pkd2-mediated Signal Transductionmentioning
confidence: 99%
“…The chest X-ray showed mild pulmonary artery expansion. The electrocardiogram showed right bundle branch block and a negative T wave in V [1][2][3] . Echocardiogram revealed a tricuspid valve regurgitation with pressure gradient of 40 mmHg.…”
Section: Case Reportmentioning
confidence: 99%
“…Tolvaptan, a vasopressin V2 receptor antagonist, selectively blocks vasopressin V2 receptors and inhibits production of cyclic adenosine 3, 5-monophosphate (cAMP). With the inhibitory mechanism on intracellular cAMP, tolvaptan is expected to prevent renal cyst growth [2]. Because there is no other effective pharmacological treatment at present, tolvaptan is recommended for patients with ADPKD who have a total kidney volume of 750 ml or more with progressive renal volume expansion [3].…”
Section: Introductionmentioning
confidence: 99%